Evaluation of Clinical and Demographic Characteristics According to Acute Coronary Syndrome Subtypes - Işık, Ömer; Ülvan, Nedret; Polat, Mete Kağan; Soydan, Elton; Ekici, Berkay; Zoghi, Mehdi (İbrahim İKİZCELİ, 2026)
Objective: Acute coronary syndromes are a group of life-threatening conditions frequently encountered in emergency departments. However, the clinical and demographic characteristics of these syndromes according to their subtypes have not been thoroughly investigated. This study examined possible differences in the clinical and demographic characteristics of ACS subtypes. Material and Method: The study included 252 consecutive patients presenting with ACS (NSTE-ACS and STEMI). Study data were obtained using a pre-prepared online case report form. The data were statistically evaluated in terms of clinical and demographic characteristics according to ACS type. Results: A total of 252 ACS patients (177 men and 75 women with a mean age of 63.2 ± 12.2 years) were included in the study. The prevalence of hypertension, hyperlipidaemia, diabetes and active smoking was 47.2%, 33.3%, 33.7% and 41.3%, respectively. At the time of admission, 40.5% of cases were diagnosed as STEMI and 59.5% as NSTE-ACS. The most common method of admission was by private vehicle (57.1%), while 31% were admitted by ambulance. Forty-five point two per cent of patients had a family history of coronary artery disease, and 23.8 per cent had undergone a cardiology clinic check-up in the past three months. A history of coronary artery bypass grafting (10.7%), stenting (34.1%) and pacemaker implantation (3.2%) was identified. Angiography was performed on 225 patients prior to discharge. Stenting was planned for 76.2% of patients, coronary artery bypass grafting (CABG) for 3.2%, and medical treatment for 11.5%. In the NSTE-ACS group, the rates of two- to three-vessel disease and CABG/medical treatment were significantly higher than in the STEMI group (p < 0.001). Male gender predominated in both groups. Conclusion: Our study found that there were some differences in clinical characteristics between STEMI and NSTEMI cases, and our results were consistent with those reported in the literature.

Amaç: Akut koroner sendromlar acil servislerde sıklıkla karşılaşılan ve yaşamı tehdit eden bir sendrom grubudur. Akut koroner sendromların klinik ve demografik özellikleri, tiplerine göre ayrıntılı olarak incelenmemiştir. Bu çalışmada, ACS tipleri arasındaki olası klinik ve demografik farklılıkları inceledik. Yöntem ve Gereç: Çalışmamıza ACS (NSTE-ACS ve STEMI) ile başvuran 252 ardışık hasta dahil edildi. Çalışma verileri, çevrimiçi olarak uygulanan önceden hazırlanmış bir vaka rapor formu kullanılarak elde edildi. Veriler, ACS tipine göre klinik ve demografik özellikler açısından istatistiksel olarak değerlendirildi. Bulgular: Çalışmaya toplam 252 AKS hastası (177 erkek, 75 kadın; ort. yaş 63,2±12,2 yıl) dahil edildi. Hastaların %47,2’sinde hipertansiyon, %33,3’ünde hiperlipidemi, %33,7’sinde diyabet ve %41,3’ünde aktif sigara kullanımı mevcuttu. Başvuru anında olguların %40,5’i STEMI, %59,5’i NSTE-AKS tanısı almıştı. En sık başvuru yöntemi özel araç (%57,1) iken, %31’i ambulansla gelmişti. %45,2 oranında ailevi KAH öyküsü, %23,8 oranında ise son 3 ayda kardiyoloji polikliniği kontrolü mevcuttu. Önceden KABG (%10,7), stent (%34,1) ve kalp pili (%3,2) öyküleri saptandı. Taburculuk öncesi 225 hastaya anjiyografi uygulanmış olup, %76,2’sine stent, %3,2’sine KABG, %11,5’ine medikal tedavi planlandı. NSTE-AKS grubunda 2-3 damar hastalığı ve KABG/medikal tedavi oranları STEMI grubuna göre anlamlı olarak daha yüksekti (p
Akut Koroner Sendrom Alt Tiplerine Göre Klinik ve Demografik Özelliklerin Değerlendirilmesi
Keywords: Cardiovascular Medicine and Haematology (Other); Kardiyovasküler Tıp ve Hematoloji (Diğer)